Analysis of Protein Thermostability Enhancing Factors in Industrially Important Thermus Bacteria Species. (January 2013) - Kumwenda, Benjamin; Litthauer, Derek; Bishop, Özlem Tastan; Reva, Oleg
Elucidation of evolutionary factors that enhance protein thermostability is a critical problem and was the focus of this work on Thermus species. Pairs of orthologous sequences of T. scotoductus SA-01 and T. thermophilus HB27, with the largest negative minimum folding energy (MFE) as predicted by the UNAFold algorithm, were statistically analyzed. Favored substitutions of amino acids residues and their properties were determined. Substitutions were analyzed in modeled protein structures to determine their locations and contribution to energy differences using PyMOL and FoldX programs respectively. Dominant trends in amino acid substitutions consistent with differences in thermostability between orthologous sequences were observed. T. thermophilus thermophilic proteins showed an increase in non-polar, tiny, and charged amino acids. An abundance of alanine substituted by serine and threonine, as well as arginine substituted by glutamine and lysine was observed in T. thermophilus HB27. Structural comparison showed that stabilizing mutations occurred on surfaces and loops in protein structures.